The impact of new cancer drug therapies on site specialised cancer treatment activity in a UK cancer network 2014–2018. (January 2020) - Bhimani, Jenna; Philipps, Lara; Simpson, Lawrence; Lythgoe, Mark; Soultati, Aspasia; Webb, Andrew; Savage, Philip
Introduction: Drug treatment for cancer has changed dramatically over the past decade with many new drugs often with multiple applications. More recently, the detailed pathway for approval from the National Institute for Health and Care Excellence (NICE) in the UK has been simplified. To explore how these changes have impacted on systemic anti-cancer therapy tumour site-specific prescribing and workload activities, we have reviewed the prescribing records for 2014–2018 in a UK cancer network. Methods: Information about the numbers of new systemic anti-cancer therapy drugs and NICE approvals were obtained from print editions of the British National Formulary (BNF) and the NICE website. Data on the numbers of new chemotherapy courses and individual treatment-related attendances were obtained from the cancer network Chemocare electronic prescribing system. Results: During the five-year study period, there were 49 new systemic anti-cancer therapy drugs for all tumour types, and a total of 65 NICE technology approvals for solid tumour indications. Overall numbers of treatment courses increased by 40.7% and total treatment-related visits by 80.6%. There was a wide variation across tumour types with the highest number of increased visits seen for melanoma (349.3%) and prostate cancer (242.3%), but in contrast, no appreciable increases were seen for lower gastrointestinal cancers or small cell lung cancer. Conclusion: The study confirms the major impact of the arrival of new drug technology and positive NICE appraisals on increasing systemic anti-cancer therapy prescribing and chemotherapy unit activity. The data in this study may be of help in planning for future service delivery planning and workforce configurations.